IMPLEMENTASI IDENTIFIKASI DAN TRACKING SASARAN SECARA OTOMATIS PADA ROBOT TEMPUR CIA VERSI N2MR3 DENGAN MENGGUNAKAN METODE PATTERN RECOGNITION - Achmad Nisar Syamsuddin; Eko Kuncoro; Prisca Chorina (Pustaka Poltekad, 2021)
The ability of weaponry and technology in the world today has increased drastically where it is used to combat and defense, to improve the staff and material capabilities of Indonesia Military ranks, in general, the Army, which serves as state defense in protecting the territorial integrity of the Republic of Indonesia. Indonesia Army troops as the vanguard are always required to be professional in always carrying out high-risk tasks after the command over with high responsibility successfully. War (OMP) is an area that will be attacked or occupied by troops as a base and defended if the task still requires it. Activities carried out in operations such as issuing combat robots to find and track targets both during the day and at night automatically from threatening enemies. Therefore we need a tool that can help in carrying out tasks during the day and night. Tracking is the process of tracking and locking the target, which can be used to track and lock an object. One example of tracking is object tracking, security at night has both advantages and disadvantages, especially in conditions with very low light intensity. So night vision is needed to become a more effective security camera. Based on these problems, a study was made on bringing about automatic target identification and tracking on the N2MR3 a version of the CIA combat robot using the pattern recognition method to maximize security in conditions with very low intensity. The results of the study indicate that this study provides results in reading objects in light and dark conditions.